Sensitivity Analysis between Lagrange Multipliers and Consumer Budget: Utility Maximization Case - Mohajan, Haradhan Kumar; Mohajan, Devajit (Annals of Spiru Haret University. Economic Series, 2023)
In this paper sensitivity analysis between Lagrange multipliers and total budget is discussed. The method of Lagrange multipliers is a very useful and powerful technique in multivariable calculus. In mathematical economics, utility is the vital concept that increases or decreases overall happiness of the consumers. This study tries to discuss utility maximization policy of an organization by considering two constraints: budget constraint and coupon constraint. In this article, an attempt has been taken to achieve the best result through the application of scientific method of optimization.